2015
DOI: 10.1093/hmg/ddv186
|View full text |Cite
|
Sign up to set email alerts
|

Gene × dietary pattern interactions in obesity: analysis of up to 68 317 adults of European ancestry

Abstract: Obesity is highly heritable. Genetic variants showing robust associations with obesity traits have been identified through genome-wide association studies. We investigated whether a composite score representing healthy diet modifies associations of these variants with obesity traits. Totally, 32 body mass index (BMI)- and 14 waist–hip ratio (WHR)-associated single nucleotide polymorphisms were genotyped, and genetic risk scores (GRS) were calculated in 18 cohorts of European ancestry (n = 68 317). Diet score w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 34 publications
3
72
1
Order By: Relevance
“…Data from 177330 adults (87 % Whites, 10 % Asian, 3 % African American) did not indicate any significant interactions between the FTO variant and dietary intake of total energy, fat, protein or carbohydrate on BMI [137]. A second meta-analysis of 68317 Europeans did not detect an interaction between a 32 SNP genetic risk score and a multifactorial diet score on BMI [136]. The diet score moderated the impact of two SNPs in/near LRRN6C and MTIF3 on BMI), although these effects were nominal and the impact of these risk variants appeared to be greater among those consuming healthier diets [136].…”
Section: Obesity-predisposing Gene Variants Interact With Dietmentioning
confidence: 82%
See 2 more Smart Citations
“…Data from 177330 adults (87 % Whites, 10 % Asian, 3 % African American) did not indicate any significant interactions between the FTO variant and dietary intake of total energy, fat, protein or carbohydrate on BMI [137]. A second meta-analysis of 68317 Europeans did not detect an interaction between a 32 SNP genetic risk score and a multifactorial diet score on BMI [136]. The diet score moderated the impact of two SNPs in/near LRRN6C and MTIF3 on BMI), although these effects were nominal and the impact of these risk variants appeared to be greater among those consuming healthier diets [136].…”
Section: Obesity-predisposing Gene Variants Interact With Dietmentioning
confidence: 82%
“…Despite the many studies demonstrating that diet patterns can moderate the genetic risk for obesity, two recent meta-analyses did not detect significant interactions between diet patterns and obesity-associated gene variants [136,137]. Data from 177330 adults (87 % Whites, 10 % Asian, 3 % African American) did not indicate any significant interactions between the FTO variant and dietary intake of total energy, fat, protein or carbohydrate on BMI [137].…”
Section: Obesity-predisposing Gene Variants Interact With Dietmentioning
confidence: 87%
See 1 more Smart Citation
“…Approaches include quantitative genetics studies, usually undertaken in twin or familybased cohorts [4,6,7,[34][35][36][37][38] and candidate gene studies, focused on individual genetic variants, haplotypes, or genetic risk scores constructed from variants with high biological priors for interactions or those conveying genome-wide < p < 5x10 TC, total cholesterol; TG, triacylglycerol significant marginal effects [39][40][41][42][43][44][45][46][47]. Several quantitative genetic studies have shown that physical activity attenuates the influence of genetic effects on cardiometabolic traits [4,6,34,35,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Although several candidate gene studies have focused on gene-diet interactions (e.g. [43][44][45][46][47] ) are marked with an asterisk (SBP for class 1 interactions, and weight for class 2 interactions). α G , γ G and λ parameters were calculated based on individuals 30-60 years of age, as this was the age range in the dataset.…”
Section: Discussionmentioning
confidence: 99%